Effective Surveillance That “Doesn’t Work”: Inferences and Social Control in New York City Public Housing - Lisa Lucile Owens (Socius, 2024)
In New York City, public housing residents are subject to constant, concentrated electronic surveillance that is beset by inequalities in application and the potential for adverse outcomes. In the literature, there is little insight into either the process by which such systems function or the impacts of this intensified exposure. This article explores, in particular, the role of inference in determining the effectiveness of surveillance. Through an analysis of qualitative data gathered through interviews with public housing residents, this article argues that surveillance, notwithstanding its actual function, is associated with powerful inferences about its functional possibilities. Findings address a source of endogeneity in existing surveillance-related studies, demonstrating how inferences about electronic surveillance notwithstanding their actual surveillant functionality may be related to the use of avoidance practices.